(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2023)
Doxorubicin (DOX) is an antineoplastic drug with potent cardiotoxic activity due to selective accumulation and disruption of mitochondrial functioning in cardiomyocytes. Accumulating evidence indicates that DOX can also induce genotoxic side effects in other cells. The mutagenic effects of DOX in human peripheral blood leukocytes and THP-1 leukemia cells were analyzed using PCR. It was revealed that DOX could induce deletions of different sizes and loci of mitogenomes of normal human leukocytes and THP-1 leukemic cells.